An analysis of the Practice and Standard of Corporate Governance in the UAE Banking Industry - Al Moosawi, Hassan (2012)
The global economic crisis of 2008, partly triggered by the lack of stringent management oversight of large financial institutions has raised regulatory alarms around the world. To address the challenges arising out of this global crisis a number of proposals to improve bank corporate governance have been put forward by international organizations. Against this backdrop this study is set, to critically study and evaluate corporate governance in a UAE bank. As part of the study thorough literature review will be conducted to study the Corporate Governance policies and practices adopted by banks in general and furthermore best practices in Corporate Governance in the banking industry will be reviewed. The data for this study is collected from both primary and secondary sources. Primary data will be collected through a questionnaire survey. The questions included in the survey were designed based on the BASEL Corporate Governance Guidelines as well as the surveys conducted by OECD MENA. Secondary data is collected from various finance journals, online library resources, the internet, books and the internal documents of the bank. The findings of the survey will be tabulated and analysed. A detailed discussion will be presented along with a set of recommendations that if applied will further improve corporate governance in the UAE banking industry.